Efektivitas Pemberian Terapi Suportif dalam Menurunkan Ansietas pada Remaja - Edo Gusdiansyah; Weni Mailita; Yuanita Ananda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Mental disorders are behavioral or psychological patterns shown by individuals that cause distress, dysfunction; reduce the quality of life which becomes a psychosocial problem. Psychosocial problems that result in social changes in society can cause mental disorders. The prevalence of adolescents in Indonesia experiencing psychosocial problems is 8.7%. In West Sumatra Province, the population is 5.48 million with a number of teenagers around 511.8 people. Of these, one in five adolescents has psychosocial problems that require adequate and special treatment. The solution to this problem is by providing supportive therapy which aims to help deal with mental health problems that exist in the community. This activity was carried out on February 3, 2021 with a total of 20 teenagers. The results of the evaluation show that there is a change in anxiety in adolescents. Suggestions for the health center are to monitor the results of this education.